Exploiting the fungal highway: development of a novel tool for the in situ isolation of bacteria migrating along fungal mycelium. Issue 11 (2nd October 2015) - Simon, Anaele; Bindschedler, Saskia; Job, Daniel; Wick, Lukas Y.; Filippidou, Sevasti; Kooli, Wafa M.; Verrecchia, Eric P.; Junier, Pilar
Abstract : Fungi and bacteria form various associations that are central to numerous environmental processes. In the so-called fungal highway, bacteria disperse along fungal mycelium. We developed a novel tool for the in situ isolation of bacteria moving along fungal hyphae as well as for the recovery of fungi potentially involved in dispersal, both of which are attracted towards a target culture medium. We present the validation and the results of the first in situ test. Couples of fungi and bacteria were isolated from soil. Amongst the enriched organisms, we identified several species of fast-growing fungi ( Fusarium sp. and Chaetomium sp.), as well as various potentially associated bacterial groups, including Variovorax soli, Olivibacter soli, Acinetobacter calcoaceticus, and several species of the genera Stenotrophomonas, Achromobacter and Ochrobactrum . Migration of bacteria along fungal hyphae across a discontinuous medium was confirmed in most of the cases. Although the majority of the bacteria for which migration was confirmed were also positive for flagellar motility, not all motile bacteria dispersed using their potential fungal partner. In addition, the importance of hydrophobicity of the fungal mycelial surface was confirmed. Future applications of the columns include targeting different types of microorganisms and their interactions, either by enrichment or by state of the art molecular biological methods. Abstract : A novel method to enrich bacteria moving along fungal mycelium. Abstract :